2019
DOI: 10.3390/bios9040136
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Analysis of Various Cancer Cell Types Immobilized in 3D Matrix and Cultured in 3D-Printed Well

Abstract: Cancer cell lines are important tools for anticancer drug research and assessment. Impedance measurements can provide valuable information about cell viability in real time. This work presents the proof-of-concept development of a bioelectrical, impedance-based analysis technique applied to four adherent mammalian cancer cells lines immobilized in a three-dimensional (3D) calcium alginate hydrogel matrix, thus mimicking in vivo tissue conditions. Cells were treated with cytostatic agent5-fluoruracil (5-FU). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Bioelectric profiling of cancer cell responses to chemotherapeutic agents is an emerging research field, as indicated by another report [ 32 ] by our group of authors where impedance spectroscopy was applied in order to study interactions between the anticancer cytostatic agent 5-fluoruracil (5-FU) and four adherent mammalian cancer cells lines were immobilized in a three-dimensional (3D) calcium alginate hydrogel matrix, thus mimicking in vivo tissue conditions.…”
Section: Results-discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioelectric profiling of cancer cell responses to chemotherapeutic agents is an emerging research field, as indicated by another report [ 32 ] by our group of authors where impedance spectroscopy was applied in order to study interactions between the anticancer cytostatic agent 5-fluoruracil (5-FU) and four adherent mammalian cancer cells lines were immobilized in a three-dimensional (3D) calcium alginate hydrogel matrix, thus mimicking in vivo tissue conditions.…”
Section: Results-discussionmentioning
confidence: 99%
“…Human neuroblastoma cell line SK-N-SH (ATCC ® HTB-11™), HeLa cervical cancer cells (ATCC ® CRM-CCL-2™), triple positive breast cell line MCF-7 (ATCC ® HTB-22™), and triple negative MDA-MB-231 (ATCC ® HTB-26™) were cultured in an incubator at 37 °C, 5% CO 2 as described previously [ 32 ]. Doxorubicin hydrochloride (>98.0%) (DOX) (Fluka Chemie GmbH, Buchs, Switzerland) was initially dissolved in dimethylsulfoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured in T-75 flasks (Sarstedt AG & Co. KG, Nümbrecht, Germany) in an appropriate incubator with humidified atmosphere at 37 °C and 5% CO 2 . Regular subcultures (twice a week) were conducted at a 1:10 ratio [ 106 ] and the adherent cells were detached from the flask by trypsinization using trypsin/ethylenediaminetetraacetic acid (EDTA) for 10 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Our research group has previously employed this approach to characterize interactions between breast cancer cells and different chemotherapeutical agents [24,25] as well as neuronal cells and neurotransmitters [26]. In the present study, we compared the Salmonella infection progression in the human colon cancer cell line Caco-2 and the mucus-secreting HT29-MTX-E12, after treatment with a different bacterial multiplicity of infection (MOI) by assessing the alterations of frequencies recordings with impedance spectroscopy measurements.…”
Section: Introductionmentioning
confidence: 99%